Assessment of Impacts of Coal Mining–Induced Subsidence on Native Flora and Native Forest Land: A Brief Review - Vishwakarma A.K.; Rai R.; Sonkar A.K.; Behera T.; Shrivastva B.K. (My University, 2025)
As compared to the surface mining, underground mining may has less impact on surroundings, but it results in land subsidence, and if it occurs in forest areas, then it may has a devastating effect on the forest land. Despite rising concerns for global food security and growing demand for coal production, less attention has been paid to the changes occurred in the soil of forest lands due to mining subsidence. The objective of this study is to scrutinize the existing information of the subsidence impact on forest lands. The literatures available internationally from journals and conferences were surveyed to review the various impacts of mining subsidence on forest land throughout the domain. The findings showed that there were quite a lot of impacts on the topography, hydrology, and soil properties. The effects were due to water logging, altered topography due to greater erosion, modified soil, and groundwater hydrology and generations of cracks or compactions that resulted in soil chemical and physical changes. The growth may also be reduced due to changes in the mining practices that are suited to subsided non-uniform landscapes. These multiple impacts need to be considered under local levels, with particular concern to the interaction of subsidence disturbances with the forest ecosystems. Therefore, proper adaptation strategies and future research directions need to be developed for such areas in the event of subsidence for the appropriate sustenance of healthy forest environments. © 2021 Scrivener Publishing LLC.